Identification of a RelA/SpoT Homolog and Its Possible Role in the Accumulation of Astaxanthin in Haematococcus pluvialis - Jin, Hui; Lao, Yong Min; Zhou, Jin; Cai, Zhong Hua (Frontiers in Plant Science, 2022)
A RelA/SpoT homolog, HpRSH, was identified in Haematococcus pluvialis. HpRSH was found to catalyze Mg2+-dependent ppGpp synthesis and Mn2+-dependent ppGpp hydrolysis，respectively. The transcription of HpRSH was significantly upregulated by environmental stresses, such as darkness, high light, nitrogen limitation and salinity stress. The intracellular ppGpp level was also increased when exposed to these stresses. Additionally, the classic initiator of stringent response, SHX, was found to upregulate the transcription of HpRSH and increase the level of ppGpp. Moreover, stringent response induced by SHX or environmental stresses was proven to induce the accumulation of astaxanthin. These results indicate that stringent response regulatory system exists and may be involved in the regulation of accumulation of astaxanthin in H. pluvialis. Furthermore, stringent response was unable to induce the accmulmulation of astaxanthin under dark condition. This result implied that stringent response may be involved in the regulation of astaxanthin accumulation in a light-dependent manner.